2022
DOI: 10.1088/1674-1056/ac43b2
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial defect engineering and photocatalysis properties of hBN/MX 2 (M = Mo, W, and X = S, Se) heterostructures

Abstract: Van der Waals (VDW) heterostructures have attracted significant research interest due to their tunable interfacial properties and potential in a wide range of applications such as electronics, optoelectronic, and heterocatalysis. In this work, the impact of interfacial defects on the electronic structures and photocatalytic properties of hBN/MX2(M = Mo, W, and X = S, Se) are studied using density functional theory calculations. The results reveal that the band alignment of hBN/MX2 can be adjusted by introducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Given the similar chemical characteristics of O and S, increasing efforts have been devoted to investigating SVs for metal chalcogenides. [ 154 ] Recently, novel zirconium trisulfide (ZrS 3 ) nanobelts with disulfide (S 2 2− ) and sulfide anion (S 2− ) vacancies were also proposed for PC ORR and the simultaneous oxidation of benzylamine to benzonitrile. [ 71 ] ZrS 3 with only S 2 2− vacancies was denominated as ZrSS 2− x , and the one with both S 2 2− and S 2− vacancies was named ZrS 1− y S 2− x .…”
Section: Defect Engineeringmentioning
confidence: 99%
“…Given the similar chemical characteristics of O and S, increasing efforts have been devoted to investigating SVs for metal chalcogenides. [ 154 ] Recently, novel zirconium trisulfide (ZrS 3 ) nanobelts with disulfide (S 2 2− ) and sulfide anion (S 2− ) vacancies were also proposed for PC ORR and the simultaneous oxidation of benzylamine to benzonitrile. [ 71 ] ZrS 3 with only S 2 2− vacancies was denominated as ZrSS 2− x , and the one with both S 2 2− and S 2− vacancies was named ZrS 1− y S 2− x .…”
Section: Defect Engineeringmentioning
confidence: 99%
“…[ 19 ] The corresponding DFT study suggested that the Mo sites at edges of MoS 2 were the adsorption sites for N 2 as the sites were undercoordinated and initiated NRR. Accordingly, to achieve more such Mo catalytic sites, MoS 2 nanosheets were modified through synthesis of ultrathin nanosheets [ 20 ] or morphological tuning into nanoflowers [ 21 ] . In the latter case, the barrier toward formation of *N 2 H 2 intermediates was decreased, which is the rate‐determining step (RDS) of NRR, on the Mo sites.…”
Section: Strategies For Structural Tuning Of Mo‐based Catalystsmentioning
confidence: 99%
“…11 Compared to polar (0002) AlN, the growth of high-quality single-phase semi-polar (112̄2) AlN is more difficult because of the anisotropic migration of adsorbed atoms on the growth surface. 12 Moreover, various crystal orientations such as (112̄2), (101̄3), and (101̄1) AlN are all possible to appear on m -plane sapphire substrates, resulting in polycrystalline AlN. 13,14 Researchers have achieved single-crystal (112̄2) AlN using metal–organic chemical vapor deposition (MOCVD) with pre-treatments such as sapphire nitridation and buffer layer introduced prior to AlN deposition.…”
Section: Introductionmentioning
confidence: 99%